(untitled) (Estudos do CEPE, 2012)
The world lives a context of energetic pre-crisis, and Brazil has discovered new big reserves of the “black gold”, which led to changing the regulation framework of its exploitation in the country. This paper focuses on the last change in that framework, in 1997, and tries to evaluate its effects in the production and its links to the rest of Brazilian economy. Using data derived from the I-O matrix in the supply side, and Balance of Payments data, we try to see if there were meaningful changes in the period 1998-2007 from the period 1990-1997 in terms of the oil sector linkage to the rest of the economy, technological modernization, its relation to employment and average earnings , and its impacts in the external insertion of the country (exports and dividends balance).